2002
DOI: 10.1253/circj.66.600
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Low-Dose Amiodarone on Atrial Fibrillation or Flutter in Japanese Patients With Heart Failure.

Abstract: The efficacy and safety of amiodarone in the management of atrial fibrillation (AF) or flutter in 108 Japanese patients with heart failure was retrospectively examined. Thirty-four (41%) of the 82 patients who were in sinus rhythm after 1 month of amiodarone administration had their first recurrence, 70% of cases occurring within 1 year of initiation. The cumulative rates of maintenance of sinus rhythm were 0.68, 0.55, and 0.47 at 1, 3, and 5 years, respectively. Amiodarone was more effective in maintaining si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
11
1

Year Published

2005
2005
2021
2021

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 40 publications
(51 reference statements)
1
11
1
Order By: Relevance
“…37) Other studies in small numbers of Japanese patients with atrial tachycardia found that 2.7-3.6% of patients receiving amiodarone developed pulmonary toxicity during mean follow-up periods of 30-36 months. 14,38) In the present study, the incidence of pulmonary toxicity was 1.4% per year, which is not low in comparison to American and European data. 37) These findings suggested that we should reduce the incidence of amiodarone-induced pulmonary toxicity because there is no safe dose of amiodarone therapy, at least in Japanese patients.…”
Section: Discussioncontrasting
confidence: 59%
“…37) Other studies in small numbers of Japanese patients with atrial tachycardia found that 2.7-3.6% of patients receiving amiodarone developed pulmonary toxicity during mean follow-up periods of 30-36 months. 14,38) In the present study, the incidence of pulmonary toxicity was 1.4% per year, which is not low in comparison to American and European data. 37) These findings suggested that we should reduce the incidence of amiodarone-induced pulmonary toxicity because there is no safe dose of amiodarone therapy, at least in Japanese patients.…”
Section: Discussioncontrasting
confidence: 59%
“…Other studies in small numbers of Japanese patients with atrial tachyarrhythmia show that 2.7-3.6% of patients receiving amiodarone developed APT during mean follow-up periods of 30-36 months. 16,17 Although the backgrounds, number of subjects, or follow-up periods were different, there is a relatively high incidence of APT in Japanese patients. The reason why it should be higher than in previous reports from Europe and the United States, despite the extremely low dose of amiodarone used in Japanese patients, is unclear.…”
Section: Circulation Journal Vol71 October 2007mentioning
confidence: 99%
“…1 This is highlighted by the high rates of discontinuation often observed in clinical trials of rhythm-control therapies, reportedly due to adverse events and lack of efficacy. [5][6][7][8][9] A study of 481 patients with atrial fibrillation enrolled in the Fibrillation Registry Assessing Costs, Therapies, Adverse Events and Lifestyle (FRACTAL) who began to receive antiarrhythmic drugs between 1997 and 2000 demonstrated that at 1 year, the percentages of patients who had discontinued therapy were as high as 68% for class Ia antiarrhythmics (disopyramide, procainamide, quinidine), 41% for class Ic antiarrhythmics (encainide, flecainide, propafenone), 36% for sotalol, and 18% for amiodarone. 10 However, to the best of our knowledge, no large-scale studies have examined the rate and temporal patterns of discontinuation of rhythm-control therapies for atrial fibrillation in current clinical practice in the United States.…”
mentioning
confidence: 99%